2005
DOI: 10.1158/0008-5472.can-04-3822
|View full text |Cite
|
Sign up to set email alerts
|

The Growth and Metastasis of Human Hepatocellular Carcinoma Xenografts Are Inhibited by Small Interfering RNA Targeting to the Subunit ATP6L of Proton Pump

Abstract: Extracellular pH is usually low in solid tumors, in contrast to the approximately neutral intracellular pH. V-ATPase, which overly functions in some cancers with metastatic potential, plays an important role in maintaining neutral cytosolic pH, very acidic luminal pH, and acidic extracellular pH. ATP6L, the 16 kDa subunit of proton pump V-ATPase, can provide proton hydrophilic transmembrane path. In this study, ATP6L in a human hepatocellular carcinoma cell line with highly metastatic potential (HCCLM3) was kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 40 publications
8
121
1
Order By: Relevance
“…more differentiated) tumor cells. Because a peculiarity of malignant tumor cells is their ability to grow in an acidic condition (17), depending on the activity of proton pumps, we used a proton pump inhibitor (38,39) to analyze the role of low pH in favoring exosome traffic in malignant tumor cells. We found that exosome entry into target cells was significantly reduced by preincubation with proton pump inhibitors, suggesting that inhibition of extracellular acidification may interfere with exosome traffic in malignant tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…more differentiated) tumor cells. Because a peculiarity of malignant tumor cells is their ability to grow in an acidic condition (17), depending on the activity of proton pumps, we used a proton pump inhibitor (38,39) to analyze the role of low pH in favoring exosome traffic in malignant tumor cells. We found that exosome entry into target cells was significantly reduced by preincubation with proton pump inhibitors, suggesting that inhibition of extracellular acidification may interfere with exosome traffic in malignant tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of V-ATPases in cancer malignancy has been repeatedly demonstrated in several human cancer tumors and cell lines, including hepatocellular carcinoma, B-cell tumors, and melanoma (37)(38)(39). Inhibition of V-ATPase function via knockdown of the protein subunit ATP6L expression using RNAinterfering technology can effectively retard the growth and metastasis of human hepatocellular carcinoma xenografts (37). Inhibition of V-ATPase activity can also be achieved by treat- ment with proton pump inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 4T1 cells with 90% V 1 C1 depletion had significantly less metastatic potential and reduced osteolytic lesions 27. Alternatively, siRNA knockdown of the ATP6L (V o c) subunit in HCCLM3 hepatocellular carcinoma cells resulted in significantly reduced invasion, decreased MMP‐2 expression, reduced average xenograft size, and a dramatic reduction in intrahepatic metastases 56. In support of this, siRNA‐mediated knockdown of the V o c subunit led to a reduction in both SK‐N‐MC and A‐673 Ewing sarcoma cell number 47…”
Section: V‐atpase As a Potential Cancer Therapeutic Targetmentioning
confidence: 99%